Visual narrative of the pandemic as a form of health communication in the digital age - Sabri, Sabri; Adiprabowo, Vani Dias Adiprabowo (COMMICAST, 2023)
Many disease information problems are caused by a lack of knowledge and public misunderstanding of health information. Health communication includes disseminating health information to the public to achieve healthy living behaviours, creating awareness, changing attitudes and providing motivation for individuals to adopt recommended healthy behaviours to be the main objectives of health communication. This study aims to analyze the use of visual narratives in health promotion during a pandemic that focuses on non-technical aspects. In addition, knowing the health promotion strategy includes visuals, communication, and media. The research method used is qualitative. This research tries to understand phenomena in their natural setting and context, namely that researchers do not try to manipulate the observed phenomena. The data collection method in this study is observation and literature study. In this research procedure, the first stage is planning, the second stage is field data study and data analysis, and the third stage is drawing conclusions. The results showed that the Ministry of Health, through the Directorate of Health Promotion and Community Empowerment, has prepared integrated promotional facilities, including publication, print, and audiovisual media. This promotional tool is a website that can be accessed to view and download promotional media. Visual narratives are selected very comprehensively based on field data obtained from regions in Indonesia. The ignorance of health promotion workers causes the error in the use of narratives in the health promotion media in making promotional means for information of a local nature. Due to the lack of knowledge of the health promotion team in the region in choosing the right narrative for the promotional media used.